Robotics, mechatronics, and artificial intelligence : experimental circuit blocks for designers / Newton C. Braga. - Braga, Newton C. (Newnes, 2002)
This text helps hobbyists and experimenters in robotics, mechatronics and artificial intelligence to decide what skills they want to feature in a project and then pick and choose the right 'building blocks' to create the perfect results.